PERANCANGAN MENARA PENYARINGAN AIR SEBAGAI MEDIUM PEMULIHAN EKOSISTEM AIR DI DANAU CINCIN, SUNTER - Handoyo, Tiffany Yobella; Jayanti, Theresia Budi (Jurusan Arsitektur dan Perencanaan, 2025)
Jakarta, once known as the “Water City,” is now facing a clean water crisis due to massive transformations in the city’s water management system, particularly since the 20th century. Human-centered (anthropocentric) development has replaced canals with roads and eliminated many green spaces and natural reservoirs. One of the most affected areas is North Jakarta, including Danau Cincin (Cincin Lake), which is currently experiencing a decline in water quality, sedimentation, and the degradation of its aquatic ecosystem. The lack of sustainable water management efforts has led to recurring pollution and worsened inequality in access to clean water for local communities. This project responds to these conditions by proposing a regenerative solution in the form of the “Water Restoration Tower,” a multifunctional vertical structure designed as a layered water filtration system aimed at restoring the natural function of Danau Cincin as a clean water reservoir. The system integrates physical, chemical, and biological approaches using biofilters made from native plants to continuously purify the lake water. The methodology includes field surveys, water quality testing, and literature analysis, adopting frameworks such as Water Sensitive Urban Design (WSUD) and Nature-based Solutions (NbS). The project’s main innovation lies in the use of vertical design as a response to limited urban space, while positioning architecture as an ecological and educational element that strengthens the connection between humans and nature. This project aspires to become a prototype of regenerative architecture in dense urban areas, capable of restoring water’s role as a life-giving element and reinforcing the city’s environmental resilience. Keywords: biofiltration; cincin lake; jakarta as water city; regenerative; resilience anthropocentric; water filtration tower Abstrak Jakarta, yang dahulu dikenal sebagai “Kota Air”, kini menghadapi krisis air bersih akibat transformasi besar-besaran pada sistem tata air kota, terutama sejak abad ke-20. Pembangunan yang berfokus pada kepentingan manusia (antroposentris) telah mengubah kanal-kanal menjadi jalan raya dan menghilangkan banyak ruang hijau serta waduk alami. Salah satu wilayah yang terdampak adalah Jakarta Utara, termasuk Danau Cincin, yang kini mengalami penurunan kualitas air, sedimentasi, serta rusaknya ekosistem perairan. Minimnya upaya pengelolaan air berkelanjutan menyebabkan pencemaran terus berulang dan memperburuk ketimpangan akses air bersih bagi masyarakat. Proyek ini merespons kondisi tersebut dengan menawarkan solusi regeneratif berupa “Menara Restorasi Air”, yaitu struktur vertikal multifungsi yang dirancang bertujuan sebagai sistem penyaringan air berlapis untuk mengembalikan lagi fungsi alami Danau Cincin sebagai resevoir air bersih alami. Sistem ini memadukan pendekatan fisik, kimia, dan biologis menggunakan biofilter dari tanaman lokal untuk membersihkan air waduk secara berkelanjutan. Metode dilakukan melalui survei lapangan, uji kualitas air, serta analisis literatur dengan pendekatan Water Sensitive Urban Design (WSUD) dan Nature-based Solution (NbS). Inovasi utama dari proyek ini adalah penerapan desain vertikal sebagai solusi ruang terbatas di kota padat, sekaligus menjadikan arsitektur sebagai elemen ekologis dan edukatif yang memperkuat keterhubungan antara manusia dan alam. Diharapkan, proyek ini dapat menjadi prototipe arsitektur regeneratif di kawasan urban yang mampu mengembalikan peran air sebagai elemen kehidupan dan memperkuat ketahanan lingkungan kota.